Hess: The Political Theory of Shklar - Schrecker, Cherry (Serendipities. Journal for the Sociology and History of the Social Sciences, 2017)
Book review of: Hess, Andreas (2014) The Political Theory of Judith N. Shklar: Exile from Exile, Basingstoke: Palgrave Macmillan. 235 pp. ISBN: 978-1-137-03249-2. Price: $ 110,00 (Hardcover)